Current Communication Practices Between Internal Medicine Subspecialty Fellowship Applicants and Program Directors: A National Survey - Rahul Kumar Thakur; Charan Thej Reddy Vegivinti; Barun Kumar Ray; Hasiya Yusuf; Abhishek Kumar (American Journal of Medicine Open)
Purpose: As fellowship applications increasingly transition to virtual interviews, the role of social media in this process remains uncertain. This study explores internal medicine subspecialty program directors' (PDs) perspectives on current communication practices, including the use of social media and email, between applicants and programs. Method: A national survey was conducted among U.S. internal medicine subspecialty fellowship PDs from November to December 2023. The survey collected demographic information about PDs, program-level information, and their views on using social media platforms (Twitter/X and Instagram) and email for program promotion and application review. Results: Out of 297 PDs who responded (18.5% response rate), 52% were male, 69% identified as White/Caucasian, majority from age group 46-50 years. The subspecialties with the highest representation were infectious disease (15%), pulmonology and critical care (14%), and cardiology (12%). Among respondents, 41% used Twitter/X and 24% used Instagram for program promotion. A smaller fraction reviewed applicants through these platforms for interview invitations (14% via Twitter/X and 7% via Instagram). PDs reported receiving an average of 35 letters of intent emails and calling 36% of applicants for interviews. Conclusions: This study is the first to assess the value PDs place on social media and email in the fellowship application review process across various internal medicine subspecialties. While social media is a valuable tool for program promotion and engagement, traditional email outreach remains crucial in the interview selection process.